`y = -(3/(t - 2)^4)` Find the derivative of the function.

Textbook Question

Chapter 2, 2.4 - Problem 20 - Calculus of a Single Variable (10th Edition, Ron Larson).
See all solutions for this textbook.

1 Answer | Add Yours

mathace's profile pic

mathace | (Level 3) Assistant Educator

Posted on

Given: `y=-(3/(t-2)^4)`

Rewrite the equation as `y=-3(t-2)^-4`

Find the derivative using the Chain Rule.

`y'=12(t-2)^-5`

`y'=12/(t-2)^5`

We’ve answered 318,936 questions. We can answer yours, too.

Ask a question